Computer-Based Media for Learning Geometry at Mathematics Class of Secondary Schools - Yenita Roza; Putri Yuanita; Sehatta Saragih; Hadiyanta Alfajri; Andespa Saputra (Universitas Riau, 2017)
This research is aimed at developing computer-based media for mathematics learning. This media used interactive model to help students understand the topic of lines, angles and rectangular. This development research applied development model by Borg and Gallmodified by Sugiyono.The study began by finding the potentials materials and its problems followed by astudy of literature. The subject in this research is line, angle and rectangular,including rectangle, square and trapezium. Product design was done through two stages: paper-based design and computer-based. The applications used for product design are Microsoft Frontpage, Microsoft Power Point and Photoshop. Learning media were validated by three experts or validators and were revised based on the input from the validators. The revised learning media were tested on two stages: a small group test consisting of five respondens and a large grouptest consisting of forty respondens. Based on the analysis of data and discussion, it can be concluded that computer-based mediafor mathematics learning is valid with an average score of 3.17 on aspect of materials and 3.18 from aspects of media. This computer-based media formathematicslearning also had practicalities with an average score of 97,92% on a small group test and 99,22% in the large group test..